Representing American Sign Language Letters and Numbers with Humanoid Robot Arm - Gul, Mehmet (My University, 2021)
The widespread use of robotic systems is an example of increasing technological developments in daily life. The robotic systems that are accustomed to widespread use in the industry show huge impact in education, health, and many other areas nowadays. Robotic systems are no longer expensive and are not difficult to access systems that can be drawn and designed with design software like CAD programs. Within the scope of the study, major changes are made in the reference design, and Python software is used to send data to the Arduino control card that is used for control of the robotic system and to provide movement. The humanoid robotic arm developed in the study is printed with the 3D printer, sign languages that can be realized by one-handed letters among sign languages were investigated. All 26 alphabetical letters of English in American Sign Language can be demonstrated with the right hand alone. It has nearly the same principle that represents the demonstration of sign language expressions with a robotic hand, and the American Sign Language is the most widely known sign language. If experience is gained with this study, it can be used for the other sign language. In this study, audio and text messages sent over Python were performed on the humanoid robotic arm.
Keywords: Deep Learning; Sign Language; Humanoid Robotic Arm; Human-Robot Interaction; Speech-Recognition